Analisis Kinerja Keuangan Menggunakana Metode Risk Profile, Governance, Earning, Capital Pada Bank Yang Memiliki Dual Banking System di Indonesia - Donny Dwiky Desmawan (Universitas YARSI, 2021)
This study aims to measure financial performance with a composite assessment of the level of soundness of banks in Islamic and conventional commercial banks with the risk profile, governance, earnings and capital (RGEC) methods for the 2015-2019 period. The data analysis method used is comparative analysis used to compare the dependent variable with the Independent Sample t-Test) using SPSS 25 software. Variable data is based on published financial statements from 2015-2019. The results of this study indicate that of the 9 ratios analyzed, there is 1 ratio that there are differences in the financial performance of Islamic and conventional banks during the 2015-2019 period, here is no difference in the financial performance of Islamic and conventional banks for the 2015-2019 period